Pancytopenia as a presentation of B12 deficiency - Purushothaman, Prinink; K, Rijas; Ravindran, Kavya (Indian Journal of Case Reports, 2024)
We present the case of a 16-year-old boy with hemolytic anemia with investigations showing pancytopenia, which turned out to be due to B12 deficiency. Whenever we see a teenager presenting with pancytopenia, the common causes that we think of are hematologic malignancies, drug-induced cytopenias, hypersplenism, etc. Anemia as a presentation is common in B12 deficiency, yet its occurrence with jaundice is a very uncommon and easily overlooked presentation. The same is the case of B12 presenting as pancytopenia which is a well-described entity, yet omitted initially due to its uncommon nature in this modern developed world.